Ecology, security and international action: beyond sanctions on North Korea. Issue 10 (17th July 2021) - Bourdais Park, JeongWon; Bridges, Brian
Abstract: This article explores the international measures that can resolve ecological problems in a highly securitised zone, taking North Korea (DPRK) as an example. The main question posed is how effective the available international policy measures for ecological risk mitigation are in a highly securitised country. Irreversible ecological conditions and aggravating humanitarian crises co-influence each other and threaten society as a whole. The main purpose of the article is to suggest ways of mainstreaming the environmental aspect of security in international actions that engage with problematised countries like North Korea. A cross-cutting analysis is provided on the possible approaches – including environmental aid, extended or integral humanitarian exemption, and proactive ecological intervention – for the international community to be engaged in the field of environmental security under three different circumstances: peace, security alert and conflict. The current international measures employed in North Korea demonstrate that available tools are either overused or underused, thereby failing to address the interconnectivity of the triple perils for the economy, human welfare and ecosystem, and further aggravating political tensions.